Artificial light at night increases the nighttime feeding of monarch butterfly caterpillars without affecting host plant quality - Haynes, Kyle J.; Miller, Geoffrey D.; Serrano-Perez, Madaris C.; Hey, Melissa H.; Emer, Lauren K. (Basic and applied ecology, 2023)
Most research on the effects of artificial light at night (ALAN) on animal behaviour focuses on nocturnal species. In addition, there are few studies on the effects of ALAN on the feeding behaviour of herbivores or how such behavioural changes affect herbivore performance. In this study, we tested whether ALAN has direct effects on the feeding frequency and performance of the larvae of the monarch butterfly (Danaus plexippus), a species in which adults are diurnal but larvae exhibit little diel rhythm in feeding activity. We also tested for effects of ALAN on the growth, nutritional quality, or anti-herbivore defences of this herbivore's primary host plant in North America, common milkweed (Asclepias syriaca). There was no evidence that ALAN affected the growth, nutritional quality or defensive traits of the host plant. However, at night, the feeding frequency of larvae exposed to ALAN was two times higher than in larvae that were not exposed to ALAN. Despite this effect on feeding frequency, ALAN had no significant effects on larval development time (days from second instar to pupation) or pupal mass. Our study highlights that ALAN can have strong impacts on the feeding activity patterns of herbivorous insects and that these impacts are not limited to nocturnal species.